130k views
5 votes
Solving Linear Equat
Solve the linear equation:
3.4 + 2(9.7 – 4.8x) = 61.2

User FrankMonza
by
5.3k points

2 Answers

3 votes

Answer:

Explanation:

Simplifying

3.4 + 2(9.7 + -4.8x) = 61.2

3.4 + (9.7 * 2 + -4.8x * 2) = 61.2

3.4 + (19.4 + -9.6x) = 61.2

Combine like terms: 3.4 + 19.4 = 22.8

22.8 + -9.6x = 61.2

Solving

22.8 + -9.6x = 61.2

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22.8' to each side of the equation.

22.8 + -22.8 + -9.6x = 61.2 + -22.8

Combine like terms: 22.8 + -22.8 = 0.0

0.0 + -9.6x = 61.2 + -22.8

-9.6x = 61.2 + -22.8

Combine like terms: 61.2 + -22.8 = 38.4

-9.6x = 38.4

Divide each side by '-9.6'.

x = -4

Simplifying

x = -4

User Ontk
by
5.2k points
2 votes

Answer:

Explanation:

3.4 + 19.4 - 9.6x = 61.2

22.8 - 9.6x = 61.2

-9.6x = 61.2 - 22.8

-9.6x = 38.4

x = -4

User Blazing Fast
by
5.0k points